Dynamical Behavior of a Delayed Predator-prey Model in Periodically Fluctuating Environments - Moussaoui, A.; Alaoui, M. A. Aziz (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper we develop a non-autonomous predator-prey system with time delay to study the influence of water level fluctuations on the interactions between fish species living in an artificial lake. We derive persistence and extinction conditions of the species. Using coincidence degree theory, we determine conditions for which the system has at least one periodic solution. Numerical simulations are presented to illustrate theoretical results.